Complete F9 Gene Deletion, Duplication, and Triplication Rearrangements: Implications for Factor IX Expression and Clinical Phenotypes - Ma, YuXin; Li, Yang; Sun, Jie; Liang, Qian; Wu, Runhui; Ding, Qiulan; Dai, Jing (Thrombosis and Haemostasis, 2023)
Background Factor IX (FIX) plays a critical role in blood coagulation. Complete deletion of F9 results in severe hemophilia B, whereas the clinical implications of complete F9 duplication and triplication remain understudied.Objective To investigate the rearrangement mechanisms underlying complete F9 deletion (cases 1 and 2), duplication (cases 3 and 4), and triplication (case 5), and to explore their association with FIX expression levels and clinical impacts.Methods Plasma FIX levels were detected using antigen and activity assays. CNVplex technology, optical genome mapping, and long-distance polymerase chain reaction were employed to characterize the breakpoints of the chromosomal rearrangements.Results Cases 1 and 2 exhibited FIX activities below 1%. Case 3 displayed FIX activities within the reference range. However, cases 4 and 5 showed a significant increase in FIX activities. Alu-mediated nonallelic homologous recombination was identified as the cause of F9 deletion in case 1; FoSTeS/MMBIR (Fork Stalling and Template Switching/microhomology-mediated break-induced replication) contributed to both F9 deletion and tandem duplication observed in cases 2 and 3; BIR/MMBIR (break-induced replication/microhomology-mediated break-induced replication) mediated by the same pair of low-copy repeats results in similar duplication–triplication/inversion–duplication (DUP–TRP/INV–DUP) rearrangements in cases 4 and 5, leading to complete F9 duplication and triplication, respectively.Conclusion Large deletions involving the F9 gene exhibit no apparent pattern, and the extra-hematologic clinical phenotypes require careful analysis of other genes within the deletion. The impact of complete F9 duplication and triplication on FIX expression might depend on the integrity of the F9 upstream sequence and the specific rearrangement mechanisms. Notably, DUP–TRP/INV–DUP rearrangements significantly elevate FIX activity and are closely associated with thrombotic phenotypes.
Keywords: factor IX; genomic structural variation; hemophilia B; low-copy repeats; thrombosis